I soffitti a cassettoni nei palazzi della famiglia Cesi - Nocchi, Livia (Opus Incertum, 2018)
In the genre of monumental wood carved coffered ceilings some of the most significant examples can be seen in the palaces of the Cesi family, built between the seventh and ninth decades of the 16th century in Rome and in their country homes in Umbria and Lazio. The ceilings of the Acquasparta palace, probably designed by Giovan Domenico Bianchi, are great quality expressions of Roman artistic taste and their magnificence fully reflects the celebratory intention of the clients and their taste for this kind of decoration. In the case of the ceilings of Cantalupo in Sabina, some still in operation, we have detailed documentation on the sculptors and carpenters involved, including Guglielmo Della Porta and the French Stefano Possenti. As for the palazzo Armellini-Cesi in Via della Conciliazione there are two sumptuous ceilings whose decoration recalls typical models of the first half of the century. The Cesi always invested a great deal of resources in their residences for the implementation of imposing decorative systems to enhance the wealth and power of the family in Rome and the study of these ceilings and of the artists involved helps to understand the dynamics of work, of some models and their diffusion.